Ethical challenges in forensic imaging: a systematic review of key issues, emerging artificial intelligence (AI) implications and future directions - Khalid, Aina Arisha; Syed, Waliullah Shah; Sayed, Inayatullah Shah (IIUM Press, International Islamic University Malaysia, 2024)
Background: Forensic imaging is a widely employed technique in the field of forensics yet it raises numerous ethical concerns. For radiographers, ethical issues can significantly impact the credibility and reliability of their work, especially as advancements in imaging technology introduce challenges related to data manipulation and the need to balance diagnostic objectives with patient privacy. Thus, a comprehensive study of these ethical challenges is essential. Methods: A thorough literature search was conducted using Google Scholar, ScienceDirect, PubMed, and GoPubMed, focusing on "ethical issues in forensic imaging" and related terms like "ethical issues in postmortem imaging." Boolean operators and keyword variations such as "ethical issues AND forensic imaging," "forensic AND ethical issues AND radiology," and "postmortem imaging AND ethics" enhanced relevance. The search covered publications from 2003 to 2024, specifying "human" and "ethics". Articles were selected based on predefined criteria for further data extraction, synthesis, and analysis. Results: The findings reveal key ethical concerns, including the validity of tests, informed consent, privacy, confidentiality, and professionalism issues commonly identified in forensic radiographic imaging. The integration of artificial intelligence (AI) into forensic processes adds further complexity to these ethical dilemmas. Conclusion: These findings highlight the urgent need for developing robust guidelines, raising awareness, fostering cooperative environments, establishing standards, and creating centres of excellence to address the ethical challenges in forensic imaging.